Analisis Waste Dengan Pendekatan Lean Construction Pada Proyek Pembangunan Jembatan Sungai Manggar Balikpapan - Syam Bima Muhammad Akbar (INFO-TEKNIK, 2022)
According to Abduh (2007) Indonesian construction industry still has inefficiency in its implementation, which is because there is still a lot of waste on the execution. Efforts to prevent or reduce waste on the project will increase the contractor's profits and minimize the negative effect to environment (Julisa et al., 2019). One method that can be used is lean construction. lean construction has the main objective of continuously increasing production efficiency and eliminating all waste. In this study, a waste analysis using a lean construction approach was carried out which had the most influence on the Manggar River Bridge project. This study uses descriptive analysis of percentages with the aim of describing the condition of the phenomena of the variables and indicators being analyzed. After doing the analysis, it was obtained Waste Lean Construction The most influential on the Manggar River Bridge Project is Waiting with work activities stopped due to bad weather (Waiting) with an impact on this project 131 hours of work or 13.1 working days or the equivalent of 1.79% of the total working days cannot be done due to bad weather.